Fabric-based flexible thermoelectric generators: Design methods and prospects - Li, Yiping; Zeng, Jingyun; Zhao, Yang; Wang, Congran; Zhang, Chunyang; Cheng, Tingting; Tao, Junhui; Li, Jie; Wang, Chuanhui; Zhang, Lin; Chen, Xinqi (Frontiers in Materials, 2022)
At the beginning of the 21st century, micro-nano processing technology has developed rapidly, and research on wearable electronic devices has exploded. In particular, flexible thermoelectric materials and thermoelectric generators (TEGs) that have stretchable or foldable properties have been widely studied. Textile-based thermoelectric materials are more suitable for use on the human body than are film or block types of devices, and they are accordingly favoured for wearable smart devices. The design idea of textile thermoelectric materials include the preparation of thermoelectric fibres, textiles, fabric-based films and some novel methods, like using three-dimensional modules to become two-dimensional fabrics by a weaving method, which not to rely something as a base for TE modules. Investigators are thus gaining opportunities to make comfortable and effective fabric TEGs using a wider variety of materials. This article briefly introduces the common methods used to produce textile TEGs. The opportunities and challenges of fabric TEGs are discussed at the end.